Angina Hospitalization Rates in Women With Signs and Symptoms of Ischemia But no Obstructive Coronary Artery Disease: A Report from the WISE (Women's Ischemia Syndrome Evaluation) Study. Issue 4 (18th February 2020) - Aldiwani, Haider; Zaya, Melody; Suppogu, Nissi; Quesada, Odayme; Johnson, B. Delia; Mehta, Puja K.; Shufelt, Chrisandra; Petersen, John; Azarbal, Babak; Samuels, Bruce; Anderson, R. David; Shaw, Leslee J.; et al.
Abstract : Background: Recurrent hospitalization is prevalent in women with signs and symptoms of ischemia and no obstructive coronary artery disease. We hypothesized that rates of angina hospitalization might have changed over time, given advances in diagnostic and therapeutic approaches. Methods and Results: We evaluated 551 women enrolled in the WISE (Women's Ischemia Syndrome Evaluation) study with no obstructive coronary artery disease (CAD) for a follow‐up period of 9.1 years. We analyzed angina hospitalization rates using the Kaplan‐Meier method. Univariate analysis and multivariable Cox proportional hazard models were developed for prediction of angina hospitalization in women with signs and symptoms of angina and no CAD. A total of 223 women had nonobstructive CAD (>20–50% <stenosis) and 328 had no CAD (<20% stenosis). Among women with either no or nonobstructive CAD, the mean age was 56±11 years, 56% had hypertension, 46% dyslipidemia, 51% were smokers, and 10% had prior myocardial infarction. The rates of angina hospitalization for a maximum of 9.1 years showed near‐linear increases in both groups ( P =0.03). Hypertension, dyslipidemia, nonobstructive CAD, use of nitrates, statins, and angiotensin‐converting enzyme inhibitors were univariate predictors of angina hospitalization. Adjusted multivariate hazard ratios for angina hospitalization were significant for use of nitrates 2.58 (1.80–3.69, P <0.0001), statins 1.80 (1.20–2.70, P =0.004), and angiotensin‐converting enzyme inhibitors/angiotensin II receptor blockers 1.81 (1.22–2.68, P =0.003). Conclusions: Angina hospitalization rates continued at a relatively constant rate in all women with no obstructive CAD despite medical advances. Clinical trials aimed at reducing angina hospitalization rates and identifying the pathophysiological mechanisms contributing to angina symptoms in women with no CAD and women with no obstructive CAD.